Indoctrination and the Aims of Democratic Political Education: Challenges and Answers - Moilanen, Antti; Huttunen, Rauno (Wiley, 2025)
In this theoretical article, we analyze indoctrination in relation to the aims of democratic political education using a theory of indoctrination which is based on the work of J & uuml;rgen Habermas. In particular, we examine how the challenge of indoctrination is connected to the goals of democratic political education and how this issue can be avoided. We reconstruct a Habermasian concept of indoctrination and criteria for this type of teaching. Moreover, we describe central controversies in German didactic theories of political education and elucidate the theoretical premises of these theories. Lastly, we construct an account of the challenges facing democratic political education and provide solutions to these hurdles by conceptualizing how the aims of political education can be pursued as indoctrination, as well as critically of indoctrination. We find that democratic political education involves the challenges of indoctrination, but these can be avoided by teaching in a self-reflective, controversial, and dialogic manner.